Developmental coordination disorder subtypes also vary in the pattern of behavioral and emotional problems - Schoemaker, M. M.; Lust, J. M.; Steenbergen, B.; Houwen, S.; Diepstraten, J. E. M.; Wilson, P. H.; Poelma, M. (Frontiers in Psychology, 2024)
Background Behavioral and emotional problems in children with Developmental Coordination Disorder (DCD) are well documented. However, the heterogeneity of this group has been largely overlooked. Addressing this gap is important to develop individually-tailored interventions. Aims Our three aims were to assess: (i) behavioral and emotional problems in children with DCD; (ii) behavioral and emotional problems in subtypes of DCD, and (iii) the context-specificity of these problems (home/school). Methods and procedure Data were extracted from the medical records of a large sample of 93 children with DCD (79 boys, mean age 8.3) referred to a rehabilitation center. Behavioral and emotional problems were assessed with the Child Behavior Checklist (CBCL) and the Teacher Report Form (TRF). Outcomes and results Two-third of the children presented with behavioral and emotional problems according to both parents and teachers. The subtypes with generalized motor problems were most affected, while the subtype with gross-motor problems was least affected. Children presented with more problems at home than at school. Conclusion and implications Given the frequent occurrence of behavioral and emotional problems, clinicians should tailor their interventions to these problems in DCD. Knowledge of subtypes can inform these decisions.